Peran Perpustakaan Sekolah dalam Mengembangkn Literasi Membaca Siswa Kelas 3a di MIN 2 Probolinggo - Hikmah, Dewi Wihayuning; Heriadi, Didik (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2022)
Abstract Reading is one of the most important things in life. Various learning processes. By reading Various knowledge we can achieve success we can get it. This article aims to describe the implementation of the literacy movement for students in class 3a MIN 2 Probolinggo. Through various student activities, that the role of the library in developing reading literacy towards developing reading literacy of grade 3a students at MIN 2 Probolinggo plays an important role and has a positive value, the research results show that 15 minute reading activities and various methods and reading corners to develop literacy reading is an improvement plan to support the reading literacy campaign. Keywords: Education, School Libraries, Reading Literacy